HUBUNGAN ANTARA LEADER-MEMBER EXCHANGE DENGAN PERILAKU KERJA INOVATIF: STUDI PADA ANGGOTA ORGANISASI DENGAN PEMIMPIN PEREMPUAN - Alfi Mufidah; Pratista Arya Satwika; Rafika Nur Kusumawati (Universitas Muhammadiyah Lampung, 2022)
ABSTRACTThis study aims to determine the relationship between leader-member exchange and innovative work behavior among organizational members who led by female leaders. The sample in this study were 62 members of the non-government organization Gajahlahkesehatan.id. The sampling technique used in this research is simple random sampling. The instruments used were the innovative work behavior scale (r=0,953) and the leader-member exchange scale (r=0,944). Based on the results of data analysis using the product-moment correlation method from Pearson, the correlation coefficient (r) obtained is 0,292 with a significance level (p) < 0.05, which is 0,021. The research hypothesis is accepted, namely that there is a relationship between leader-member exchange and innovative work behavior among organizational members who led by female leadersKeywords: Leader-Member Exchange, Non-government Organization, Innovative Work Behavior.ABSTRAKPenelitian ini bertujuan untuk mengetahui hubungan antara leader-member exchange dengan perilaku kerja inovatif pada anggota organisasi dengan pemimpin perempuan. Sampel pada penelitian ini adalah 62 anggota non-government organization Gajahlahkebersihan.id. Teknik pengambilan sampel yang digunakan adalah simple random sampling. Instrumen yang digunakan adalah skala perilaku kerja inovatif (r=0,953) dan skala leader-member exchange (r=0,944). Berdasarkan hasil analisis data menggunakan metode korelasi product-moment dari Pearson, nilai koefisien korelasi (r) yang didapatkan adalah sebesar 0,292 dengan taraf signifikansi (p) < 0,05 yaitu sebesar 0,021. Hipotesis penelitian diterima, yaitu terdapat hubungan antara leader-member exchange dengan perilaku kerja inovatif pada anggota organisasi dengan pemimpin perempuan. Kata kunci: Leader-Member Exchange, Non-Government Organization, Perilaku Kerja Inovatif.